A Perspective on the Role of Dynamic Alternative RNA Splicing in the Development, Specification, and Function of Axon Initial Segment - Iijima, Takatoshi; Yoshimura, Takeshi (Frontiers in Molecular Neuroscience, 2019)
Alternative splicing is a powerful mechanism for molecular and functional diversification. In neurons, alternative splicing extensively controls various developmental steps as well as the plasticity and remodeling of neuronal activity in the adult brain. The axon initial segment (AIS) is the specialized compartment of proximal axons that initiates action potential (AP). At the AIS, the ion channels and cell adhesion molecules required for AP initiation are densely clustered via the scaffolding and cytoskeletal proteins. Notably, recent studies have elucidated that multiple AIS proteins are controlled by extensive alternative splicing in developing and adult brains. Here, we argue the potential role of dynamic regulation of alternative splicing in the development, specification, and functions of the AIS. In particular, we propose the novel concept that alternative splicing potentially modulates the structural and functional plasticity at the AIS.